2018
DOI: 10.1007/s11605-018-3693-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Pancreatic Cancer: from Early Detection to Treatment

Abstract: Exosomal analysis is beneficial in demonstrating mechanisms behind PC growth and metastasis, immunosuppression, drug resistance, and paraneoplastic conditions. Furthermore, the use of exosomes can be beneficial in detecting early-stage PC and exosomes have potential applications as therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 101 publications
0
37
0
Order By: Relevance
“…Several evidence suggest that exosomes analysis is beneficial for understanding the mechanisms associated with the development, metastasis, and drug resistance of PC. Meanwhile, numerous studies have reported about the possibility of using exosomal components as diagnosis biomarkers and therapeutic targets for PC . Exosomes contain a diverse array of functional biomolecules, including proteins, lipids, and nucleic acids, which are transferred from donor cells to recipient cells for modulating intracellular signaling and intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…Several evidence suggest that exosomes analysis is beneficial for understanding the mechanisms associated with the development, metastasis, and drug resistance of PC. Meanwhile, numerous studies have reported about the possibility of using exosomal components as diagnosis biomarkers and therapeutic targets for PC . Exosomes contain a diverse array of functional biomolecules, including proteins, lipids, and nucleic acids, which are transferred from donor cells to recipient cells for modulating intracellular signaling and intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes also participate in numerous important physiological and pathological processes, including intercellular communication, cell motility, angiogenesis ( 13 ), immune response ( 14 ), tumor development and metastasis ( 15 , 16 ). Owing to their bioactive cargo, exosomes may serve as messengers and may offer valuable information for the diagnosis and prognosis of disease ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, more promising results are obtained in solid tumors including those of prostate, lung, esophagus and ovary [121][122][123][124][125]. In particular, using EVs for early detection of pancreatic cancer have been studied extensively [126][127][128][129].…”
Section: Diagnostic/prognostic Potential Of Ev Biomarkersmentioning
confidence: 99%